Penginjilan Terhadap Suku Meree – Di Kabupaten Kaimana Melalui Gereja Kemah Injil Papua - Yulian Anouw (Integritas: Jurnal Teologi, 2022)
This study shows that there are cultural values ​​and worldview concepts of the Meree people who are "relatively close", namely belief in occult knowledge and still thick with local wisdom culture, and myths of warasee and expectations of ideal future persons in myths of belief and loyalty to Meree. so that it can be "meeted" with the values ​​of the Bible through the change of function. The writing method used in the field of contestual evangelism theology with descriptive analysis. The result found is that the church is never separated from the people, thus advancing the ministry. The Meree people have the belief that every people has the right to Salvation for Christ and understands the Scriptures.